Penerimaan Diri Sebagai Prediktor Fear of Negative Evaluation Pada Emerging Adulthood di Indonesia - Rafi Damri (Jurnal Kajian Ilmiah, 2024)
Emerging adulthood is a period of transition from adolescence to adulthood that generally occurs in the age range of 18-25 years. In this transition period, developmental tasks become more complex due to the demands of greater responsibilities such as education, marriage, work, and so on. Social and personal expectations put pressure on individuals emerging adulthood. If one cannot meet the expectations of others and has maladaptive perfectionism, the individual is likely to experience anxiety, including fear of negative evaluation. Fear of negative evaluation may indicate low self-acceptance. Therefore, this study aims to identify whether or not there is a relationship between self-acceptance and fear of negative evaluation in emerging adulthood. The method used is a quantitative method with a correlational design. Participants were selected through purposive sampling with the criteria of 18 to 25 years old and Indonesian citizenship. 182 participants participated in this study. Measurement of both variables in this study used the Brief-Fear of Negative Evaluation instrument (BFNE-II) and the self-acceptance sub-scale of Psychological Well-being. The hypothesis test analysis used a non-parametric correlation test, namely the Spearman Rho test. The findings of this study indicate a relationship between self-acceptance and fear of negative evaluation in emerging adulthood in Indonesia, with a significance value of ,000 and a negative nature of the relationship (-0.184). This can be an illustration of the relationship between the two variables.